Modulation of sympathoadrenergic contractions by perivascular adipose tissue in mesenteric arteries of rats with different level of body adiposity - Zemancikova, A; Torok, J; Balis, P; Valovic, P; Ulicna, O; Chomova, M (Journal of physiology and pharmacology, 2020)
Obesity is associated with increased sympathetic nervous system activation, possibly contributing to higher cardiovascular risk. The aim of this study was to assess the relationship between body adiposity and sympathoadrenergic contractions in rat isolated mesenteric arteries, and the modulatory effect of mesenteric perivascular adipose tissue (PVAT). Experiments were performed on male 38-week-old Wistar, Zucker lean (ZL) and Zucker diabetic fatty (ZDF) rats. Paired rings of isolated rat superior mesenteric arteries with or without PVAT were prepared and connected to a force-displacement transducer for the recording of isometric tension. Contractile responses were elicited by increasing doses of exogenous noradrenaline and by endogenous noradrenaline released during electrical stimulation of perivascular adrenergic nerves. In ZDF rats, mesenteric PVAT had marked anticontractile effect leading to significant reduction in adrenergic contractions of their superior mesenteric arteries; however, in arterial preparations without PVAT, obese rats showed significantly increased sensitivity in their contractile responses to adrenergic stimulation when compared to other rat groups. In Wistar rats, ranging in the level of body adiposity between ZL and ZDF rats, neurogenic contractions in arterial preparations with preserved PVAT were higher compared to those without PVAT. No vasomodulatory effect of PVAT was detected in mesenteric arteries from ZL rats. The results of this study indicate that the modulatory effect of mesenteric PVAT on arterial adrenergic contractions did not change in proportion with increasing adiposity; however, it could be influenced by the rat strain-specific distribution of sympathetic nerves between PVAT and the proper mesenteric arterial wall. In ZDF rats, characterized by higher vascular sympathetic tone, the mesenteric arteries might be specifically regulated by the anticontractile effect of PVAT, leading to higher mesenteric blood flow. This could be associated with hyperphagia and increased nutrient-induced mesenteric vasodilatation in this rat strain.
Keywords: Animals; elektrická stimulace; Electric Stimulation; Vasoconstriction; Sympathetic Nervous System; Rats, Wistar; vazokonstrikce; druhová specificita; Obesity; noradrenalin; Adiposity; Species Specificity; adipozita; potkani Zucker; Rats, Zucker; obezita; sympatický nervový systém; modely nemocí na zvířatech; Male; Disease Models, Animal; arteria mesenterica superior; mužské pohlaví; zvířata; Mesenteric Artery, Superior; Norepinephrine; potkani Wistar